Pengaruh Persepsi Wajib Pajak Mengenai Sistem Perpajakan, Tarif Perpajakan, Pemahaman Perpajakan Terhadap Perilaku Penggelapan Pajak - Muhamad Abdul Azis Azis; Arthie Arditha Rachman; Lihan Rini Puspo Wijaya (Jurnal Akuntansi Bisnis dan Ekonomi, 2022)
This study aims to determine the effect of taxpayers' perceptions of the tax system, tax rates, and understanding of taxation on tax evasion behavior in the city of Bandar Lampung. The population in this study is an individual taxpayer in Bandar Lampung. This study used a sample of 100 respondents who were calculated using the Slovin formula with the proportional random sampling method. Data was collected using a questionnaire measured by a Likert scale. The analytical technique used in this research is multiple linear regression. The results of this study indicate that the perception of taxpayers regarding the taxation system, tax rates, and understanding of taxation affect tax evasion behavior of taxpayer in Bandar Lampung.